Effect of volume-weight on apparent ileal and excreta amino acid digestibility and feeding value of barley for poultry - Perttilä, Sini; Valaja, Jarmo; Partanen, Kirsi; Jalava, Taina (The Kielanowski Institute of Animal Physiology and Nutrition, 2001)
A total of 185 Ross broiler chickens (age 22 days) and 36 adult Leghorn cockerels were used to investigate the effect of volume-weight (from 53.4 to 71.5 kg/hl) on the apparent excreta digestibility (AED) of nutrients and apparent nitrogen corrected metabolizable energy value (AMEn) of barleys. Furthermore, apparent ileal (AID) and AED of amino acids were determined for broilers. Birds were given either a semi-purified soyabean meal beased diet (crude protein 300 and 170 g/kg dry matter for broilers anc cockerels, respectively) or basal diet-barley mixtures (50:50 on a DM basis). The AID and AED of nutrients were determined using chromium mordanted straw as an indigestible marker. The AID of nutrients was measured by the slaughter technique. Volume-weight did not affect the AID or D of amino acids in broilers. Neither did volume-weight affect the AMEn of barley in broilers or cocherels. The AMEn of barleys were higher for cockerels compared to broilers. Differences in amino acid digestibility of diets measured from excreta and digesta varied for individual amino acids. The AID of alanine, glycine and methionine were higher then corresponding AED values. For other measured amino acids AED was higher than AID, the largest differences observed for cystine and spartic acid.
Keywords: Ko; siipikarja; ohra; hehtolitrapaino; sulavuus; barley; poultry; digestibility; volume-weight; amino acids; barley; digestibility; metabolizable energy; poultry; volume-weight